TANGGUNG JAWAB MASKAPAI PENERBANGAN TERHADAPAT BAGASI PENUMPANG YANG HILANG ATAU RUSAK - Agus Wijayanto, Yulius Addy; Puspawati, I Gusti Ayu (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 07, Juli 2013, 2013)
This writing shall be entitled as “Flight Aviation Liabilities towards Lost and Damaged Passengers’ Luggages “. This writing shall apply the normative analysis method combined with statutory approach. Indonesia as one of the country whose aviation business had emerged fast recently, indicated through the increasing quantity of airline services. Contrastingly, such phenomenon had been inflicted by the lack of response and seriousness of numerous aviation services in terms of claim during the lost or damaged luggages of passengers’ occured. Consequently, this condition had entered the court without any notification or understanding of the passenger concering the claim of luggage mechanism which is considered complicated and imbalance amount of compensation.
Keywords: Flight Aviation, Liabilities, Luggage